Performance Analysis and Optimization of Multi-Traffic on Communication Networks - Ponomarenko, Leonid; Kim, Che Soong; Melikov, Agassi (Springer Berlin Heidelberg : Imprint: Springer, 2010)
Promptly growing demand for telecommunication services and information interchange has led to the fact that communication became one of the most dynamical branches of an infrastructure of a modern society. The book introduces to the bases of classical MDP theory; problems of a finding optimal САС in models are investigated and various problems of improvement of characteristics of traditional and multimedia wireless communication networks are considered together with both classical and new methods of theory MDP which allow defining optimal strategy of access in teletraffic systems. The book will be useful to specialists in the field of telecommunication systems and also to students and post-graduate students of corresponding specialties.